PENGETAHUAN PENAMBANG PASIR DESA KALIURANG KECAMATAN SRUMBUNG KABUPATEN MAGELANG MENGENAI ANCAMAN LAHAR DINGIN DI KALI BEBENG GUNUNG MERAPI (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2022)
The threat of cold lava from Mount Merapi is a secondary hazard causing an increasing impact on the number of casualties. Knowledge of sand miners is the key to success in anticipating the threat of cold lava disaster. So that the sand miners are able to respond and determine the appropriate action based on the knowledge they have. The purpose of this study was to analyze the knowledge of sand miners regarding the threat of cold lava in Bebeng River. The population in this study was taken using a total sampling technique with a sample of 63 respondents in the category of traditional sand miners and modern sand miners who live in Kaliurang Village. The results show that the knowledge of sand miners is included in the fairly good category with a knowledge index value of 72%. Based on the comparison of the categories of miners, it is known that modern sand miners have a 6% higher value than modern miners. Knowledge of distance, signs and causes of cold lahar threats has higher results than knowledge of triggers of lahar threats and elements of cold lahar threats. Experience, place of residence and participation in disaster organizations greatly affect the knowledge of sand miners regarding the threat of cold lava